Tingkat Kelangsungan Hidup Dan Pertumbuhan Panjang Larva Ikan Kakap Putih (Lates calcarifer) Dengan Suhu Pemeliharaan Yang Berbeda: Tingkat Kelangsungan Hidup Dan Pertumbuhan Panjang Larva Ikan Kakap Putih (Lates calcarifer) Dengan Suhu Pemeliharaan Yang Berbeda - Kartika Dewi Cahyani Simangunsong Kartika; Muzahar; Wiwin Kusuma Atmaja Putra (Program Studi Budidaya Perairan Universitas Maritim Raja Ali Haji, 2022)
This study aims to determine the optimal temperature range of rearing media for the growth and survival of barramundi larvae. This research was conducted in the biology laboratory of the Faculty of Marine Sciences and Fisheries, Raja Ali Haji Maritime University. The test fish used were 3 day old white snapper larvae which were kept in 13 aquariums where one aquarium was specifically for organ observation. The aquarium used is 25x25x35 cm filled with 10 liters of water with a density of 5 fish/liter. The temperature treatments were P1 (26°C), P2 (28°C), control (30°C), and P4 (32°C) with 3 replications. The design used was a completely randomized design. Larvae were fed rotifers using the abliditum method with a frequency of 3 times a day. The results showed that the white snapper larvae produced a length growth rate and survival rate of 4.99 mm and 28,67 % at an optimal temperature of 32°C.